2011
DOI: 10.1001/archgenpsychiatry.2011.26
|View full text |Cite
|
Sign up to set email alerts
|

Rewarding, Stimulant, and Sedative Alcohol Responses and Relationship to Future Binge Drinking

Abstract: Context Excessive consumption of alcohol is a major problem in the United States and abroad. Despite many years of study, it is unclear why some individuals drink alcohol excessively while others do not. It has been postulated that either lower or greater acute responses to alcohol, or both, depending on the limb of the breath alcohol concentration curve, contribute to propensity for alcohol misuse. Objective To prospectively assess the relationship of acute alcohol responses to future binge drinking. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

50
489
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 346 publications
(552 citation statements)
references
References 96 publications
50
489
6
Order By: Relevance
“…In partial agreement with the differentiator model (Newlin and Thomson, 1990), recent studies have found that lower sedative response and greater stimulant response to alcohol in the lab are associated with escalate drinking and AUD symptomatology at 2 (King et al, 2011) and even 6 years post assessment . Behavioral pharmacology studies have also established SR to be highly a reliable (Roche et al, 2013) and multi-dimensional phenotype consisting of stimulation, sedation and tension relief dimensions (Ray et al, 2009).…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…In partial agreement with the differentiator model (Newlin and Thomson, 1990), recent studies have found that lower sedative response and greater stimulant response to alcohol in the lab are associated with escalate drinking and AUD symptomatology at 2 (King et al, 2011) and even 6 years post assessment . Behavioral pharmacology studies have also established SR to be highly a reliable (Roche et al, 2013) and multi-dimensional phenotype consisting of stimulation, sedation and tension relief dimensions (Ray et al, 2009).…”
Section: Introductionmentioning
confidence: 53%
“…To that end, human research has demonstrated that individuals vary dramatically in their subjective response to alcohol (SR) and that these differences are in turn predictive of one's liability for alcoholism (King et al, 2011Ray et al, 2010b;Schuckit, 1984;Schuckit and Smith, 1996). In partial agreement with the differentiator model (Newlin and Thomson, 1990), recent studies have found that lower sedative response and greater stimulant response to alcohol in the lab are associated with escalate drinking and AUD symptomatology at 2 (King et al, 2011) and even 6 years post assessment .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 'differentiator' model proposes that individuals at-risk for AUDs experience enhanced stimulant effects during the ascending limb of the blood alcohol curve and diminished sedative effects during the descending limb (reviewed in Ray et al, 2010;Newlin and Thompson, 1990;Newlin and Renton, 2010). Although there remains some uncertainty about which precise dimension of individuals' subjective reactions to alcohol is most predictive of subsequent AUDs (King et al, 2002(King et al, , 2011, there is consensus that some aspect of individual subjective response mediates the risk forFand development ofFAUDs, making such response profiles potentially interesting endophenotypes (Morean and Corbin, 2010;Ray et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a temptation to suggest that all of the pleasures of drinking come with 'moderate' consumption rather than intoxication, but the strong form of this claim has been subject to critique (Keane, 2009;Room, 2000). Instead, heavier drinkers report greater stimulant and lower sedative effects (King et al, 2011), and people expect greater levels of both happiness and misery at higher levels of consumption (Adey et al, 2010).…”
Section: Subjective Wellbeing Methodsmentioning
confidence: 99%